Analysis of hardware architecture Markovian Chain Queuing model for wireless sensor networks - Agel, Mabruka Mohamed; Habaebi, Mohamed Hadi; Hamida, Belal Ahmed (Science & Engineering Research Support soCiety (SERSC), 2017)
A wireless Sensor Network (WSN) commonly consumes fairly less energy whereas light and multiple-distributed sensors along with an appropriate wireless network usually come with a lower data rate. An increased system performance along with relatively a higher stability can be achieved by means of applying suitable routing protocol and QoS. QoS represents the effectiveness and robustness of any system concerned. The expansion in relation to productivity of a system may depend on keeping the energy consumption at a controlled level. This paper reports on a study in which quality measurement service was provided by means of analyzing packets in the queuing systems by employing queuing theory. The proposed model is two M/M/1/N queues in tandem with N buffer capacity. The simulation which was performed by MATLAB software indicated that an increase in the service rate of one of the servers while fixing the service rate of another server may result in a waste of hardware resources. Also, the blocking probability for same buffer’s size and data arrival rate will not reach less than specific values. Keywords: Blocking probability, Quality of service, Queuing theory, Wireless sensor 1networks.